Kajian Penyebaran Akuifer Menggunakan Geolistrik Dengan Metode Schlumberger Kompleks RRI Cisalak, Sukmajaya, Kota Depok, Jawa Barat - Izza H. Hanani; Wahju Krisna Hidajat; Narulita Santi (PROMINE, 2017)
The research was conducted in Cisalak area, Sukmajaya district, Depok city, West Java. The researchwas committed in order to search for water source as a purpose to support the planning in built privateuniversity in West Java. The research aims to know the spreading of the aquifer. The used method isby observing the regional geology of the area and supported by geoelectric measuring and water tabledata.. This research used Schlumberger method which spreaded in 10 measuring points. From thismethod, the assessed litologi were clay, tuff sandy, and conglomerat. The underground correlationwas committed in four sections. The aquifer generally tend to spread from the central from west toeast of the area and from north to south.